"A better human being:" Diaspora images of the New Israeli Woman. Issue 2 (3rd July 2019) - Grimmeisen, Julie
ABSTRACT: This article explores Western Jews' admiration for the new State of Israel on the basis of women's representation. Pamphlets, biographies, and whole series of fundraiser films, produced by Zionist women's organizations, depicted Jewish-Israeli women as carriers of democratic values, caring mothers for all of Israel's population, and courageous fighters for their people's survival. The Jewish-Israeli woman's image as "a better human being" served as an intriguing symbol through which Diaspora Jews could identify with the Jewish state and overcome feelings of impotence after the Holocaust in Europe. The idealized representation of Jewish-Israeli women primarily suited Western Jewry's need for Jewish empowerment.